Architecture Of The Normative-Legal Information System, Methodological Provision Of Educational And Methodological Work Of The Institution Of Higher Education (Journal of Information Technologies in Education (ITE), 2009)
Purpose, functions, structure, electronic documents base contents and main issues of hardware and software architecture of the normative-legal information system, educational and methodological work of the institution of higher education are developed.
Keywords: architecture; database; information system; educational and methodological work